Alignment of the External Evaluation and Specific Features of Waldorf1 Pedagogy - Andrea Liszka; Erika Kopp (University of Lower Silesia, 2016)
Evaluation and assessment have increasing importance in education. Because of an international trend toward greater school autonomy, evaluation and assessment is fueling a need to monitor how schools are doing as, simultaneously, with demand is increasing for effectiveness, equity and quality in all fields of education, whether mainstream or alternative (OECD, 2013). This study aims to observe the state-required external evaluation of Waldorf kindergartens in Berlin, until now the only case in international practice in which the state has evaluated Waldorf/Steiner institutions' professional work. The main question is how these institutions can preserve their own profiles during the external evaluation process. This question also has great importance in Hungary because a new state evaluation system has recently been introduced that will concern the Waldorf/Steiner schools.